Effect of Glass Fiber Post Surface Treatment on Bond Strength of a Self-Adhesive Resin Cement: An “In Vitro” Study - Lairds Rodrigues dos Santos; Darlon Martins Lima; Edilausson Moreno Carvalho; Vandilson Pinheiro Rodrigues; Claudia Maria Coelho Alves (International Journal of Dentistry)
Objective. This study evaluated the influence of different mechanical and chemical surface treatments alone and combined with silane on the bond strength (BS) of glass fiber posts (GFPs) using self-adhesive resin cement. Methods. Eighty-four single-rooted bovine teeth (six groups, n = 14) were submitted to BS analysis after GFP cementation. The treatments applied in the studied groups were no surface treatment (control), silane (S), 24% hydrogen peroxide (PER), 24% hydrogen peroxide and silane (PER + SIL), blasting with 50 μm aluminum oxide particles (BLAST), and blasting with 50 μm aluminum oxide particles and silane (BLAST + SIL). Results. BS differed significantly among groups (p < 0.001). It was higher in the SIL (10.5 ± 3.5 MPa), BLAST + SIL (11.5 ± 3.2 MPa), and PER + SIL (11.6 ± 4.6 MPa) groups than in the control (6.5 ± 2.9 MPa), BLAST (8.6 ± 4.0 MPa), and PER (7.1 ± 2.8 MPa) groups, with no significant difference among groups receiving silanization. Cement post adhesive failure was more common in the SIL, BLAST, and PER + SIL groups, and cement-dentin adhesive failure was more common in the control, BLAST + SIL, and PER groups. Conclusion. These results show that silane application alone increases BS.